2012
DOI: 10.1111/chf.12001
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profile in Persons With Systolic and Diastolic Heart Failure

Abstract: Persons with heart failure (HF) have four times the risk of having cognitive impairment compared with the general population and display different patterns of cognitive impairment. This secondary analysis of a published cross-sectional study of 90 community-dwelling adults examined the Montreal Cognitive Assessment (MoCA) scores and HF differentiated as systolic and diastolic HF. Mean MoCA score was 22.9 (standard deviation±2.31) in persons with systolic HF (n=69) and 24.8 (standard deviation±2.76) in persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 39 publications
1
33
1
2
Order By: Relevance
“…There are very limited data on evaluation of cognitive function in patients with preserved ejection fraction [3335]. The study that most directly addresses cognitive impairment in HFpEF patients also used the MoCA instrument [33].…”
Section: Discussionmentioning
confidence: 99%
“…There are very limited data on evaluation of cognitive function in patients with preserved ejection fraction [3335]. The study that most directly addresses cognitive impairment in HFpEF patients also used the MoCA instrument [33].…”
Section: Discussionmentioning
confidence: 99%
“…For quantitative variables arithmetic mean (± standard deviation) or median (interquartile range) were calculated as appropriate, and P values derived from a two-sample t -test (U-Mann–Whitney tests were used for skewed data). For qualitative variables, percentages within specified groups were calculated and P values were derived using Chi [2] tests. All the tests were two-sided; differences were considered significant at the p <  0.05 level.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of CI depends on the test used and varies widely among studies, ranging from less than 30 % to more than 80 % [27]. As cognitive tests are age-and education sensitive [8] the use of a validated screening test in our population would provide valuable information on CI prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, research has shown that cognitive impairment is prevalent in HF, although substantial variability in the pattern of deficits has been reported. 1,2 According to a review by Pressler 3 , 25%e50% of HF patients experience cognitive impairment. Moreover, according to one study, hospitalized HF patients with cognitive impairment have a 5-fold increased mortality.…”
mentioning
confidence: 99%